2016
DOI: 10.18632/oncotarget.12394
|View full text |Cite
|
Sign up to set email alerts
|

Combined targeting of SET and tyrosine kinases provides an effective therapeutic approach in human T-cell acute lymphoblastic leukemia

Abstract: Recent evidence suggests that inhibition of protein phosphatase 2A (PP2A) tumor suppressor activity via the SET oncoprotein contributes to the pathogenesis of various cancers. Here we demonstrate that both SET and c-MYC expression are frequently elevated in T-ALL cell lines and primary samples compared to healthy T cells. Treatment of T-ALL cells with the SET antagonist OP449 restored the activity of PP2A and reduced SET interaction with the PP2A catalytic subunit, resulting in a decrease in cell viability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 59 publications
(110 reference statements)
1
18
0
Order By: Relevance
“…Small-molecule SET inhibitors have already been identified, and they have shown promise in inhibiting oncogenic signaling and malignant cell behavior [21,32,[44][45][46]. In accordance with the major theme of this review, a recent study demonstrated that combination of SET targeting and tyrosine kinase inhibitor provides an effective therapeutic approach in human T-cell acute lymphoblastic leukemia [34]. Apart of small-molecules targeting the PIPs, the novel series of orally bioavailable and nontoxic PP2A reactivator molecules with profound in vivo therapeutic activities in KRAS mutant lung cancers and castration-resistant prostate cancer [47,48], provide a very encouraging example that PP2A indeed is druggable [14,39].…”
Section: Therapeutic Targeting Of Pp2asupporting
confidence: 53%
“…Small-molecule SET inhibitors have already been identified, and they have shown promise in inhibiting oncogenic signaling and malignant cell behavior [21,32,[44][45][46]. In accordance with the major theme of this review, a recent study demonstrated that combination of SET targeting and tyrosine kinase inhibitor provides an effective therapeutic approach in human T-cell acute lymphoblastic leukemia [34]. Apart of small-molecules targeting the PIPs, the novel series of orally bioavailable and nontoxic PP2A reactivator molecules with profound in vivo therapeutic activities in KRAS mutant lung cancers and castration-resistant prostate cancer [47,48], provide a very encouraging example that PP2A indeed is druggable [14,39].…”
Section: Therapeutic Targeting Of Pp2asupporting
confidence: 53%
“…T-ALL constitutes 10-15% of childhood ALLs and 25% of adult ALLs. An effective chemotherapy combination for T-ALL has not been developed yet, and firstline therapy fails in 25% of pediatric and more than 50% of adult cases [1,2]. Recent studies have demonstrated that new treatments targeting specific genes or molecular pathways in cancer patients are more efficient and less toxic.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that new treatments targeting specific genes or molecular pathways in cancer patients are more efficient and less toxic. Thus, targeted treatment and the determination of related oncogenes have a priority in terms of patient survival and occurrence of toxicity [2]. Therefore, new treatment options should be developed for these cases by determining new molecular targets.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In AML, SET is highly dependent on MYC-transcriptional activity and recruitment of RUNX1 and GATA2 on its promoter [102]. By impairing SET binding to PP2A, with molecules like FTY720 [82,105], CM-1231 [106], or OP449 [107,108] it is possible to re-establish PP2A activity, inhibiting tumor growth [91,109] and overcoming therapeutic resistance in preclinical models [92,108]. SET is known to interact with SETBP1 (SET-binding protein 1), which protects SET from protease cleavage.…”
Section: Arpp19mentioning
confidence: 99%